Glucagon-Like Peptide 1 Recruits Microvasculature and Increases Glucose Use in Muscle via a Nitric Oxide–Dependent Mechanism - Chai, Weidong; Dong, Zhenhua; Wang, Nasui; Wang, Wenhui; Tao, Lijian; Cao, Wenhong; Liu, Zhenqi (Diabetes (New York, N.Y.), 2012)
Glucagon-like peptide 1 (GLP-1) increases tissue glucose uptake and causes vasodilation independent of insulin. We examined the effect of GLP-1 on muscle microvasculature and glucose uptake. After confirming that GLP-1 potently stimulates nitric oxide (NO) synthase (NOS) phosphorylation in endothelial cells, overnight-fasted adult male rats received continuous GLP-1 infusion (30 pmol/kg/min) for 2 h plus or minus NOS inhibition. Muscle microvascular blood volume (MBV), microvascular blood flow velocity (MFV), and microvascular blood flow (MBF) were determined. Additional rats received GLP-1 or saline for 30 min and muscle insulin clearance/uptake was determined. GLP-1 infusion acutely increased muscle MBV (P < 0.04) within 30 min without altering MFV or femoral blood flow. This effect persisted throughout the 120-min infusion period, leading to a greater than twofold increase in muscle MBF (P < 0.02). These changes were paralleled with increases in plasma NO levels, muscle interstitial oxygen saturation, hind leg glucose extraction, and muscle insulin clearance/uptake. NOS inhibition blocked GLP-1-mediated increases in muscle MBV, glucose disposal, NO production, and muscle insulin clearance/uptake. In conclusion, GLP-1 acutely recruits microvasculature and increases basal glucose uptake in muscle via a NO-dependent mechanism. Thus, GLP-1 may afford potential to improve muscle insulin action by expanding microvascular endothelial surface area.